ANALISIS FINANSIAL PEMBANGKIT LISTRIK TENAGA SAMPAH MENGGUNAKAN TEKNOLOGI ORGANIC RANKINE CYCLE (ORC) - Hannabila, Fairiza
As the time goes by, human needs to energy grow significantly as the number of human in the world increases. This makes the availability of non-renewable energy sources such as fossil fuels decrease. One solution offered to solve this problem is with using renewable energy to generate electricity, for example, using waste to energy power plant. Besides answering energy problems, waste to energy power plant could solves environmental matter as well since notwell- managed wastes could affect many problems for human life. One technology that is being developed for renewable energy application is organic rankine cycle (ORC). The fundamental difference between the basic rankine cycle and organic rankine cycle is its working fluids. In this research, two different circuits will be simulated, Original ORC and ORC with recuperator. Those two circuits will be compared for three different working fluids, R245fa, R1233zd, and R121b. Thus, those six circuits will be analyzed from economics perpective, by counting LCOE, and financial perspective, by couting NPV, PP, and IRR. Afterall, we’ll see whether this project is worthy or not.